Problem-Based Learning in the UbD Framework to Improve Listening and Critical Thinking: A Classroom Action Research - Qudsiyah, Zuhriyatun Nur; Hidayanti, Ika; Santoso, Widyana Putri (Abjadia : International Journal of Education, 2025)
The aim of this study is to improve students' listening comprehension and critical thinking skills by implementing the Problem-Based Learning (PBL) model within the Understanding by Design (UbD) framework in an eighth-grade EFL class at SMPN 13 Malang. The study was motivated by students’ low listening comprehension and underdeveloped critical thinking skills. A Classroom Action Research (CAR) design was used, consisting of two cycles, each involving the stages of planning, action, observation, and reflection. Data were collected through listening tests, classroom observations, critical thinking rubric, and student interviews, and analyzed using descriptive quantitative and qualitative methods. The results showed a significant improvement in students’ listening performance, with the class average increasing from 67 in the diagnostic pretest to 82 in the final task of Cycle 2. Critical thinking scores also improved across all indicators, particularly in interpretation and explanation, as students engaged in structured group work with cognitive role assignments, which also contributed to a more student-centered learning environment. The study concludes that the integration of PBL within the UbD framework effectively enhanced both listening and critical thinking skills in the EFL context. These findings suggest that structured, problem-based instruction can support competency-based goals in a junior high school English classroom.